Women Political Empowerment in Makran (Journal of Social Sciences Review, 2023)
Women's political participation is crucial for the promotion of gender equality and democratic governance. However, women are often underrepresented in political positions and face numerous barriers to participation. This paper aims to examine women's political empowerment and their participation in Makran division of Balochistan and identify strategies for promoting it. The study uses quantitative survey in which 310 questionnaires were distributed in three districts of Makran. The collected data was analyzed in SPSS software. The results show that the women in Makran are not empowered politically, but there is a good environment of politics and women have political awareness in the region. The findings of the present study have significant implications for civil society organizations, policymakers and women's rights advocates who are seeking to encourage women's political participation and gender equality.
Keywords: Women; Politics; Empowerment; Makran; Balochistan